2013
DOI: 10.1080/01635581.2013.783602
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidin B2 3,3-di-O-gallate, a Biologically Active Constituent of Grape Seed Extract, Induces Apoptosis in Human Prostate Cancer Cells Via Targeting NF-κB, Stat3, and AP1 Transcription Factors

Abstract: Recently, we identified procyanidin B2 3,3″-di-O-gallate (B2G2) as most active constituent of grape seed extract (GSE) for efficacy against prostate cancer (PCa). Isolating large quantities of B2G2 from total GSE is labor intensive and expensive, thereby limiting both efficacy and mechanistic studies with this novel anti-cancer agent. Accordingly, here we synthesized gram-scale quantities of B2G2, compared it with B2G2 isolated from GSE for possible equivalent biological activity, and conducted mechanistic stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…Specific polyphenol compounds found in grapes, including quercetin, procyanidin B2, resveratrol and epicatechin are bioactive, and can regulate apoptotic, oxidative stress and inflammatory pathways [23]. Molecular targets of grape-derived compounds include key pro-survival molecules, such as glycogen synthase kinase 3β (GSK3β) [24] and the transcription factor STAT3 [25], among many others. Interestingly, modulating both GSK3β and STAT3 has been shown to improve photoreceptor survival [26].…”
Section: Discussionmentioning
confidence: 99%
“…Specific polyphenol compounds found in grapes, including quercetin, procyanidin B2, resveratrol and epicatechin are bioactive, and can regulate apoptotic, oxidative stress and inflammatory pathways [23]. Molecular targets of grape-derived compounds include key pro-survival molecules, such as glycogen synthase kinase 3β (GSK3β) [24] and the transcription factor STAT3 [25], among many others. Interestingly, modulating both GSK3β and STAT3 has been shown to improve photoreceptor survival [26].…”
Section: Discussionmentioning
confidence: 99%
“…This deregulation of TFs contributes to tumor development by promoting the expression of oncogenic proteins and inhibiting tumor suppressor genes [9]. Many TFs, including STAT family members, serum response factors, NF-kB, and AP1, contribute to the development of various human cancers in this way, while the expression of many tumor suppressor proteins, such as GATA4 and Dickkopf-related proteins, is inhibited during carcinogenesis [10-12]. Despite recent progress in identifying the cellular events and mechanisms underlying the development of various liver cancers, the molecular mechanisms of HB development and progression have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…Matrigel were procured from BD Biosciences (San Jose, CA). B2G2 was synthesized according to the method published recently [32]. B2G2 stock solution was prepared in DMSO and stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we evaluated the potential anti-angiogenic efficacy of one such phytochemical namely Procyanidin B2 3,3″-di-O-gallate (B2G2) (Fig 1A) in various established angiogenesis-related cell culture models. B2G2 has been identified by our laboratory as the most active constituent of grape seed extract (GSE), a naturally occurring dietary agent with proven potential against various malignancies including PCA [3032]. Earlier, we have shown that B2G2 is effective against various PCA cells such as LNCaP, C4-2B, DU145 and PC-3 by causing growth inhibition and inducing apoptosis in these cells; however, its anti-angiogenic activity is still unknown [31, 32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation